2012
DOI: 10.7314/apjcp.2012.13.10.4905
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on Associations Between Nine SNPs and Glioma Risk

Abstract: Aim: Glioma cancer is the most common type of adult brain tumor. Recent genome-wide association studies (GWAS) have identified various new susceptibility regions and here we conducted an extensive analysis of associations between 12 single nucleotide polymorphisms (SNPs) and glioma risk. Methods: A total of 197 glioma cases and 197 health controls were selected, and 9 SNPs in 8 genes were analyzed using the Sequenom MassARRAY platform and Sequenom Assay Design 3.1 software. Results: We found the MAF among sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
4
30
1
1
Order By: Relevance
“…Although previous studies explored the association between XRCC3 and risk of glioma have shown the polymorphisms in rs3212092, rs861530 and rs861539 of XRCC3 are associated with glioma (Kiuru et al, 2008;Custódio et al, 2012;Liu et al, 2012;Zhou et al, 2012). A recent study conducted in China has indicated the rs861539 is associated with glioma risk (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies explored the association between XRCC3 and risk of glioma have shown the polymorphisms in rs3212092, rs861530 and rs861539 of XRCC3 are associated with glioma (Kiuru et al, 2008;Custódio et al, 2012;Liu et al, 2012;Zhou et al, 2012). A recent study conducted in China has indicated the rs861539 is associated with glioma risk (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies explored the association between XRCC3 and risk of glioma have shown the polymorphisms in rs3212092, rs861530 and rs861539 of XRCC3 are associated with glioma (Kiuru et al, 2008;Custódio et al, 2012;Liu et al, 2012;Zhou et al, 2012). A recent study conducted in China has indicated the rs861539 is associated with glioma risk (Liu et al, 2012). Another study conducted in Brasil has shown that patients with Met of the XRCC3 Thr241Met polymorphism have a significantly 3.13-fold risk of tumor development, which suggests that XRCC3 Thr241Met polymorphism is involved in susceptibility for developing astrocytomas and glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the XRCC1 Arg194Trp variant located in the proliferating cell nuclear antigen (PCNA) binding region, which suggests that this mutation may be result in gliomagenesis. However, these studies have failed to yield a consistent conclusion (Kiuru et al, 2008;Liu et al, 2009;McKean-Cowdin et al, 2009;Rajaraman et al, 2010;Custodio et al, 2011;Hu et al, 2011;Zhou et al, 2011;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013;Wang et al, 2012;Xu et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…According to the inclusion and exclusion criteria, a total of nine publications with 3,752 Cases and 4,849 Controls were included in this meta-analysis (Wang et al, 2004;Kiuru et al, 2008;Liu et al, 2009;Zhou et al, 2009;Rajaraman et al, 2010;Custódio et al, 2012;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013). Among the nine studies, four studies (Zhou et al, 2009;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013) were performed in Asian populations and four (Wang et al, 2004;Kiuru et al, 2008;Liu et al, 2009;Rajaraman et al, 2010) were conducted in Caucasian populations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the nine studies, four studies (Zhou et al, 2009;Liu et al, 2012;Luo et al, 2013;Pan et al, 2013) were performed in Asian populations and four (Wang et al, 2004;Kiuru et al, 2008;Liu et al, 2009;Rajaraman et al, 2010) were conducted in Caucasian populations. Five of the studies (Wang et al, 2004;Zhou et al, 2009;Rajaraman et al, 2010;Liu et al, 2012;Luo et al, 2013) were hospital-based and four (Kiuru et al, 2008;Liu et al, 2009;Custódio et al, 2012;Pan et al, 2013) were population-based. The genotype distributions in the controls were conformed to the HWE in all studies.…”
Section: Study Characteristicsmentioning
confidence: 99%